What have you left behind - Maqtari, Bushra Al.; Hussain S.wad (USA : Fitzcarraldo Publisher, 2018)
In 2015, a year after it started, Bushra al-Maqtari decided to document the suffering of civilians in the Yemeni civil war, which has killed over 200,000 people according to the UN. Inspired by the work of Svetlana Alexievich, she spent two years visiting different parts of the country, putting her life at risk by speaking with her compatriots, and gathered over 400 testimonies, a selection of which appear in What Have You Left Behind.
Memoir.
Text in English
Keywords: Politics Book